Exploring the Impact of Reading Motivation on Academic Achievement Among 3rd Grade Students Using Univariate and Bivariate Analysis - Widyaningsih, Yuli; Nugroho, Ikhlasul Ardi (Universitas Pendidikan Indonesia, 2025)
This study explores the impact of reading motivation and academic performance among third-grade students. The problem addressed in this research is the limited understanding of how reading motivation influences students' performance, particularly in the context of early education. The background highlights the importance of intrinsic motivation in learning, with previous studies indicating that motivated students are more likely to engage with educational materials and perform better academically. This study employs a quantitative approach, using both univariate and bivariate analyses to assess the distribution of reading motivation and its effect on academic performance. A total of 27 third-grade students were surveyed on their reading motivation, and their academic performance was analyzed. The findings reveal that 59.3% of students exhibited high reading motivation, with 63% showing high academic performance. The logistic regression analysis further shows a significant association between reading motivation and performance (p-value = 0.004), with students exhibiting high motivation more likely to perform well academically. This research contributes to the growing body of literature on the role of motivation in educational outcomes, emphasizing the need for fostering intrinsic reading motivation to improve academic performance. It also provides practical implications for educators and policymakers, encouraging the creation of supportive environments that promote reading engagement and motivation.